Experimental investigation on the formation mechanism of the TiFe alloy by the molten-salt electrolytic titanium concentrate - Shi R.; Bai C.; Hu M.; Liu X.; Du J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The ferrotitanium alloy was prepared in the molten CaCl2 system, in which resolidified ilmenite and the graphite crucible were used as cathode and anode. In this study, the electrolytic voltage was fixed at 3.1V, and three different temperatures were applied: 850oC, 875oC and 900ºC. Finally, the product was examined by SEM and XRD to determine the phase transformation after the electrolysis. The results show that the ilmenite was firstly reduced to Fe, and finally the TiFe alloy was formed. The intermediate products include CaTiO3, TiO2, Ti2O3, TiO, Fe, TiFe2, and Ti. Different product and structure can be obtained by changing temperature. According to thermodynamic calculation, the principal electroreduction products are Ti and TiFe2 and then Ti and TiFe2 are formed by interdiffusion which is governed by temperature.